(untitled) (Research, Society and Development, 2020)
Objective: To analyze the scientific knowledge online published on transvestites and transsexual women’s access to primary health care services. Method: The electronic databases Lilacs, Cochrane, Medline, SciELO, BDENF, and Google Scholar were searched. It was applied the following expressions: primary health care, transgender persons, health services accessibility, health services for transgender persons. Online full text of the articles available in Portuguese, English, and Spanish was selected. Studies were characterized according to country, year of publication, and type of study. Based on a critique, the contents were summarized into categories. Results: A total of eight (8) texts were integrated into three categories: access as a construct should be extended, the profile of health services used by transvestites and transsexual women, and barriers to the population access the health services. Conclusion: The available studies are incipient regarding the barriers of access to health services by those women, especially in primary healthcare.